PENGARUH SERTIFIKASI GURU TERHADAP MUTU PENDIDIKAN DI UPTD SD NEGERI 122345 PEMATANGSIANTAR - Simanjuntak, Melvin; Jennyfer Simanjuntak; Yustina Jenetri; Arta Sibatuara; Fitriyah Zahkiyah; Rosmeri Finondang; Desi Oktavia Lumbanraja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to explain the effect of teacher certification on the quality of education at UPTD SD NEGERI 122345 Pematang Siantar. The method used in this research is a descriptive method with a quantitative approach. The total population was 13 respondents with data collection techniques using questionnaires and data analysis techniques. Based on the research results, there is a significant influence of Teacher Certification on the quality of education at UPTD SD NEGERI 122345 Pematang Siantar.